Incessant School Closure and Quality of Learning in Universities - Success Ayodeji Fasanmi (Studies in Learning and Teaching, 2024)
The learning process at any level of education is expected to be smooth, stable and sustainable. This largely determines the effectiveness and quality of such a learning process. This study investigated the influence of incessant closure on the quality of learning in Nigerian universities. This study was hinged on the Behaviourist Theory of Learning which was considered most suitable. The descriptive survey research design was adopted for this study. Obafemi Awolowo University, Nigeria was purposively selected because the university has one of the highest incidences of disruption of academic activities in the country. Six faculties were selected out of the existing thirteen faculties while 360 students (60 from each faculty) were selected for the study. A self-designed and validated questionnaire was used to collect data for the study. The data collected were analysed using inferential statistics. The findings of this study showed that unresolved industrial disputes and students’ protest are the main causes of the frequent closure of universities which over the years have had negative influence on the quality of learning in Nigeria Universities. The study recommended the need for improved funding of the education sector, especially higher education which is critical for the development of any nation.